ANALYSIS OF CONTENT DESIGN OF SUNDANESE ETHNOMATHEMATICS LEARNING THROUGH ENDOG-ENDOGAN GAMES IN DEVELOPING CREATIVE THINKING ABILITY IN CLASS II ELEMENTARY SCHOOL STUDENTS - Fitri, Elita Nur; Supriadi, Supriadi (Didaktika, 2023)
Culture-based mathematics learning can be applied in learning because culture develops around students. Ethnomathematics is culture-based learning that can be done as an alternative to developing teaching materials. Ethnomathematical learning needs to be done to introduce the culture that surrounds students and is associated with learning, one of the cultures that surround students is traditional games. The traditional endog-endogan game can be used as an ethnomathematical learning innovation in subtraction material to help develop students' creative thinking skills. The indicators of creative thinking skills in the research used are fluency, flexibility, and elaboration. This study uses a qualitative approach with the content analysis method. The data analyzed is secondary data in the form of Learning Obstacles totaling 31 data, initial didactic design data 25 data, didactic design revision data 6 data and pedagogics of teachers and students during the learning process. Based on the results of the didactic and pedagogic design analysis. Based on the results of the analysis on the learning obstacle, students have difficulty when making stories in different forms and students only write stories in the same from the questions given, in the initial didactic design students' learning barriers began to decrease, seen from the many student responses that matched predictions, in the revision didactic design of student answers that are by predictions. Based on the results of the reflection, students wrote that the learning process was very fun. Learning mathematics will be easy for students to understand if it is supported by the teaching materials used during the learning process. The role of the teacher during the learning process can make a good relationship between students and the learning material.